PP.10.15: RISK OF EARLY VASCULAR AGEING IN NORMOTENSIVE SUBJECTS. (June 2015) - Castellaro, C.; Gonzalez, S.; Kempny, P.; Forcada, P.; Svane, J. Chiabaut; Obregon, S.; Kotliar, C.
Abstract : Objective: Early vascular aging (EVA) is closely related with a worse cardiovascular outcome. Although hypertension is clearly associated with EVA, there is a cluster of normotensive patients with EVA. In these subjects there is not well know the role of different biomarkers and risk factors as mechanism of the increased arterial stiffness. a-To evaluate the prevalence of abnormal PWV in normotensives. b-To determine independent predictors of increased vascular stiffness in normotensive, Design and method: We evaluated 136 subjects in a primary cardiovascular prevention program, without any pharmacological treatment. After applying exclusion criteria (hypertension, diabetes, kidney disease) a final sample of 85 were included (45, 5.6 ± 11.7 years, 119.8 ± 8.42/75.4 ± 8.08 mm Hg, 49% female). We performed the following determinations in all population: PWV (Mobil-O-Graph®), waist circumference, BMI, total cholesterol, LDLc, HDLc, triglycerides, glucose, A1C Hb, and information about first degree family history of hypertension and cardiovascular disease. Abnormal PWV was defined as those values above 90 th percentile (ESH). Univariate correlations between PWV and all the metabolic determinants (Pearson) were performed. Multivariate analysis to identify abnormal PWV predictors were done with logistic regression by considering: a) PWV as a dependant variable, and b) metabolic markers that showed p < 0, 1 in univariate analysis. Results: The prevalence of abnormal PWV was 11, 76%. In univariate analysis, in normotensive subjects we observed that abnormal PWV was associated with age, waist circumference, SBP, LDLc, and glucose levels. In the logistic regression, only SBP (p = 0, 02), and glucose levels (p = 0, 05) showed an independent and predictive value to determine abnormal PWV (p = 0, 0026). Figure. No caption available. Conclusions: We found that systolic blood pressure and glycemic values are closely related with early vascular aging among normotensive young and healthy subjects, independently of hypertension and cardiovascular history. We consider that larger studies could evaluate if the increased glucose values, in normotensive and non diabetic subjects, may play a role in vascular stiffness and may be a terapeutic target.